Establishing a community of practice of researchers, practitioners, policy-makers and communities to sustainably manage environmental health risks in Ecuador - Henry Bonnie; Orrego Elena; Rojas Alejandro; Yassi Annalee; Parra Jorge; Solis Fernanda; Beltran Efrain; Breilh Jaime; Spiegel Jerry M; Bowie William R; Pearce Laurie; Gaibor Juan; et al. (BMC, 2011)
Abstract Background The Sustainably Managing Environmental Health Risk in Ecuador project was launched in 2004 as a partnership linking a large Canadian university with leading Cuban and Mexican institutes to strengthen the capacities of four Ecuadorian universities for leading community-based learning and research in areas as diverse as pesticide poisoning, dengue control, water and sanitation, and disaster preparedness. Methods In implementing curriculum and complementary innovations through application of an ecosystem approach to health, our interdisciplinary international team focused on the question: "Can strengthening of institutional capacities to support a community of practice of researchers, practitioners, policy-makers and communities produce positive health outcomes and improved capacities to sustainably translate knowledge?" To assess progress in achieving desired outcomes, we review results associated with the logic framework analysis used to guide the project, focusing on how a community of practice network has strengthened implementation, including follow-up tracking of program trainees and presentation of two specific case studies. Results By 2009, train-the-trainer project initiation involved 27 participatory action research Master's theses in 15 communities where 1200 community learners participated in the implementation of associated interventions. This led to establishment of innovative Ecuadorian-led master's and doctoral programs, and a Population Health Observatory on Collective Health, Environment and Society for the Andean region based at the Universidad Andina Simon Bolivar. Building on this network, numerous initiatives were begun, such as an internationally funded research project to strengthen dengue control in the coastal community of Machala, and establishment of a local community eco-health centre focusing on determinants of health near Cuenca. Discussion Strengthening capabilities for producing and applying knowledge through direct engagement with affected populations and decision-makers provides a fertile basis for consolidating capacities to act on a larger scale. This can facilitate the capturing of benefits from the "top down" (in consolidating institutional commitments) and the "bottom up" (to achieve local results). Conclusions Alliances of academic and non-academic partners from the South and North provide a promising orientation for learning together about ways of addressing negative trends of development. Assessing the impacts and sustainability of such processes, however, requires longer term monitoring of results and related challenges.